An analysis of griefs and griefing factors - George, William (Frontiers in Blockchain, 2023)
We consider griefing factors, a measure of the cost-effectiveness of sabotage that has been used to analyze attack resistance of blockchain systems. Attackers are said to "grief" if they accept to do economic harm to themselves in order to harm others, and the griefing factor is the ratio of the harm done to the victim to the harm taken on by the attacker. In this work, we study mathematical properties of this notion, particularly considering how the presence of players willing to perform griefs at varying griefing factors impacts the equilibria present in games.